2018
DOI: 10.1186/s13567-018-0545-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative liver transcriptome analysis in ducklings infected with duck hepatitis A virus 3 (DHAV-3) at 12 and 48 hours post-infection through RNA-seq

Abstract: Duck hepatitis A virus 3 (DHAV-3), the only member of the novel genus Avihepatovirus, in the family Picornaviridae, can cause significant economic losses for duck farms in China. Reports on the pathogenicity and the antiviral molecular mechanisms of the lethal DHAV-3 strain in ducklings are inadequate and remain poorly understood. We conducted global gene expression profiling and screened differentially expressed genes (DEG) of duckling liver tissues infected with lethal DHAV-3. There were 1643 DEG and 8979 DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Similarly, pathway enrichment analysis for 7,717 DEGs of the transcriptome produced similar results. This pathway enrichment result is also consistent with another study that investigated the transcriptome of DHAV-3 infected ducklings at 48 hpi [9]. Previous reports have…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, pathway enrichment analysis for 7,717 DEGs of the transcriptome produced similar results. This pathway enrichment result is also consistent with another study that investigated the transcriptome of DHAV-3 infected ducklings at 48 hpi [9]. Previous reports have…”
Section: Discussionsupporting
confidence: 92%
“…hpi [9]. Previous reports have shown that these pathways are involved in the host anti-virus processes [31][32][33][34].…”
Section: Discussionmentioning
confidence: 97%
“…DHAV-3 causes acute hepatitis and induces typical duckling liver lesions, which is characterized by petechial hemorrhages of the liver surface [8]. The results of detecting DHAV-3 loads in the liver exhibited that the virus could replicate rapidly in the liver [9]. In addition, the highest viral titer was detected in the liver among DHAV-3 infected organs in vivo [10].…”
mentioning
confidence: 99%
“…Transcriptome analysis is a promising tool that can provide a comprehensive understanding of the molecular mechanisms involved in speci c biological processes and diseases [17]. Previous studies have described the transcriptome pro le of DHAV-, Reovirus-and DHBV-infection in ducks [18][19][20][21]. In the present study, transcriptome sequencing was employed to explore and compare the gene expression patterns of infection with different subtype DHAV-1 in duck pancreatic tissues, with the aim to compare different molecular events during DHAV-1s infection.…”
Section: Discussionmentioning
confidence: 99%